JESUS CHIEF EXECUTIVE OFFICER DALAM KONTEKS MANAJEMEN MODERN DAN IMPLIKASINYA BAGI ORANG MUDA KATOLIK - Fransiskus Janu Hamu (Biro Pengelolaan Penelitian dan Pengabdian Kepada Masyarat SETIA Ngabang, 2022)
This community service report reviews the concept of Jesus' Chief Executive Officer (CEO) in the context of modern management and its relevance to young Catholics. Through research and literature studies, we investigate how management principles such as leadership, decision-making, empowerment, and service reflected in the teachings and actions of Jesus can be applied in the daily lives of young Catholics. In modern management, which is often oriented towards material success, involving Jesus as the example of chief executives provides an alternative view that reinforces spiritual and ethical values in their decision-making and work. Using modern management principles inspired by the teachings of Jesus can provide guidance and inspiration for young Catholics as they build careers and serve others. In this context, Jesus' leadership, which is based on service, empowerment, and love, becomes a relevant model for young Catholics who wish to integrate the values of the Catholic faith into their professional world. This report provides new insights into how young Catholics can apply management principles that are morally and spiritually meaningful, and support their personal development as responsible public servants.